Guide about Computer Hardware - Novi Tri Romadhona; Masduki Asbari (Journal of Information Systems and Management (JISMA), 2022)
The purpose of this research study is the development of the world of information technology followed by the development of supporting components of technology, one of which is computers. More and more applications demand we have to use the appropriate computer hardware as well. Therefore, to provide more basic understanding to users in understanding the important parts of a computer.